The Menace of Vote Buying in Nigeria Electoral System: Issues, Causes and Solutions 2015-2023 - Vincent Eseoghene Efebeh; Benjamin Okhawere Ohis (Universitas PGRI Madiun, 2023)
Vote-buying and other forms of electoral inducements are common phenomenon in Nigerian politics. This is so because the average voter is not only poor but also illiterate and unable to resist the alluring effects of uncontrolled electoral gratifications that come in cash or kind or both. Vote-buying is inherently a derivation of election fraud. Vote buying is the root cause of bad governance and a facilitator of the imposition of the incorrect and incompetent group of individuals to fill positions in governance. This study examines the menace of vote buying in Nigeria electoral system with focus on the issues, possible causes and solution within a defined period. The study revealed that the ripple effects of vote-buying which sterns from bad governance includes the insecurity of lives and properties, wide spread corruption and general lack of accountability by the ruling elite. It further revealed that the menace breeds incompetent leadership, and incompetence breeds illiteracy, unemployment, and poverty. The paper suggests among other things that the deployment of modern technologies to enable prospective voters vote from their homes using their phones would be the game changer for future elections in Nigeria